Fabrication of multilayer and silver oxide nanowires using electro-chemical deposition in the anodic aluminum oxide template - Tawana, Ibrahim (Universitas Sebelas Maret, 2023)
In this paper, to fill molds, we have applied the electrochemical deposition method. The electrochemical deposition method to produce nanowires is performed by three different methods. We have examined the pulsed periodic method, and we have managed to fabricate the multilayer nanowires Ag/Co/Zn. Then, the produced nanowires are confirmed by the SEM and XRD analyses. Also, by putting the sample containing nanowires of Ag in the oven, the oxidation happened, and the nanowires of silver oxide are fabricated and confirmed by the XRD diffraction pattern.